2024
DOI: 10.1039/d4lc00311j
|View full text |Cite
|
Sign up to set email alerts
|

Switching to external flows: perturbations of developing vasculature within chicken chorioallantoic membrane

Prasanna Padmanaban,
Danny van Galen,
Nasim Salehi-Nik
et al.

Abstract: The impact of fluid flow shear stresses, generated by the movement of blood through vasculature, on the organization and maturation of vessels is widely recognized. Nevertheless, it remains uncertain whether...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recent studies show that mechanical forces like pressure [21,22] , compression [4,23,24] , and stretch are crucial in molding the vascularized tissue shapes. Recently, we have demonstrated that the development and organization of vascular networks during embryogenesis are adaptable to flow-induced shear stresses and can be altered by externally induced flows [25,26] . In engineered microtissues, local mechanical strain emerging from compaction and cellular traction forces on the extracellular environment induce tissue deformation, leading to changes in topology and organization of vasculature [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that mechanical forces like pressure [21,22] , compression [4,23,24] , and stretch are crucial in molding the vascularized tissue shapes. Recently, we have demonstrated that the development and organization of vascular networks during embryogenesis are adaptable to flow-induced shear stresses and can be altered by externally induced flows [25,26] . In engineered microtissues, local mechanical strain emerging from compaction and cellular traction forces on the extracellular environment induce tissue deformation, leading to changes in topology and organization of vasculature [8] .…”
Section: Introductionmentioning
confidence: 99%